Sphygmomanometer Sphygmomanometer with Led Bar Display to Improve the Blood Pressure Reading Accuracy - Bambang Guruh Irianto Guruh Irianto; Sumber Sumber; Elmira Rofida Al Haq; Mansour Asghari (Jurnal Teknokes, 2022)
Instruments in the hospital environment have a role to help and promote more accurate diagnosis and treatment. The general condition of the equipment used and their delivery are very important for a good prognostic. One of them is a device to measure blood pressure called a sphygmomanometer. There are 3 types of sphygmomanometer, namely digital, mercury, and aneroid. Currently, digital sphygmomanometers are known to be easy to use, but their accuracy is low and reduces the ability of nurses to identify blood pressure in humans. Mercury sphygmomanometer has high accuracy, but should not be used because it still uses mercury as a display. This is supported by the Ministry of Health's program to free the world of health from mercury because of the impact of mercury on health and the importance of nurses to train the skills of nurses. The purpose of this study was to reduce the use of mercury which is harmful to humans, in addition to training the nurse's ability to take blood pressure readings on patients. The method used by the researcher is to test the suitability value of the module with the calibrator and to collect data on six respondents to compare the module with the sphygmomanometer that has been traded. The result of the research is the error value when testing the module's suitability value with the DPM (Digital Pressure Monitor) calibrator with a range from 0 to 0.67%. each set point has a different error value. and the lowest error value is among the six set points, namely 0% and the highest error value is 0.67%. Meanwhile, the lowest error value in systole is 0.2% and the highest error value is 2.16%. While the lowest error value in diastole is 0% and the highest error value is 5.55%. Based on the results of the research that has been carried out, the authors conclude that this module is made to replace mercury which is prohibited from being used because it is dangerous for humans and trains nurses' abilities in determining blood pressure readings.